(untitled) (The Pretoria Student Law Review, 2023)
This article explores and analyses the concept of justice in postapartheid South Africa and whether the 1996 Constitution of the Republic of South Africa is just. This is done through critical analysis and juxtaposition of the varieties of justice presented by constitutional optimists and constitutional abolitionists. The paper will show how the principles of Ideal Theory and Non-Ideal Theory feature in the political narratives of the constitutional optimists and abolitionists, respectively. Further, this paper allows for introspection surrounding the conception of justice and how justice is realised in society. Finally, it will be argued that the conception of justice that manifests in society is subjective to the interests of the agents that hold the economic means to influence political power.